Book Tax Differences, Debt Levels, and Liquidity Influence Earnings Persistence of Companies - Zulpahmi Zulpahmi; Sumardi Sumardi; Rynzani Ayustika Putri (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
The purpose of this study is to analyze and find out whether book tax differences, debt levels and liquidity pose significant influence on earnings persistence during the period of 2013- 2017. The population in this study was 16 companies. The research sample involved 6 companies, which was determined by purposive sampling method. The present study was quantitative in nature, involving SPSS 25 upon its data analysis. Based on data analysis, the results show that book tax differences does not affect earnings persistence. Debt levels has a significant negative effect on earnings persistence. The findings also point out that liquidity have negative significant effect on earnings persistence.